Determining the norm values of table tennis in motor and technical tests in male students aged between 7-9 and analyzing differences Kosovo table tennis norm values for physical fitness and technical characteristics - Berisha, Milaim; Abazi, Blerta (VIREF Revista de Educación Física, 2021)
Objective: the study aimed to norm the physical and technical characteristics of table tennis in male students aged 7-8-9 years old. Besides this, the study also aimed to analyze the differences between motor and technical characteristics of male students between the ages of 7-8-9 living in Kosovo in table tennis. Methods: the study included 56 non-athlete boys aged 7, and 25 non-athlete boys aged 8, and 31 non-athlete boys aged 7. The Sprint (S), Vertical jump (VJ), Throwing ball (THB), Speed While Dribbling (SWD), Aiming At Target (AT), Ball Skills (BS), Eye Hand Coordination from 1 meter (EHC_1m), and Eye Hand Coordination from 2 meters (ECH_2m) were used as the measurement tools. Based on the skewness and kurtosis values, and sample groups (N), Kruskal-Wallis and One- Way ANOVA, Post-hoc (Tamhane’s T2) analyses were used to determine the differences between age groups in the motor and technical tests. Determination of the normative values was made by using the frequency and percentile values divided into 20 portions (percentiles). Results: based on the results of the data analyses of the study, there are significant differences in motor and technical abilities related to table tennis between 7-8-9 years old children. Conclusion: the norm values related to the table tennis branch for motor tests (sprint, vertical jump, ball throwing), technical tests (speed while dribbling, aiming to target, ball skills), and motoric (reactional) tests (eye-hand coordination from 1 meter and eye-hand coordination form 2 meters) were determined. The norm values were determined in 4 groups, for which separate data in 20% piece represented the percentiles for each test.